Pelatihan dan peluang bekerja kembali pekerja formal di era pandemi Covid-19 - Aditya Putri, Fitriani; Padang Wicaksono (Jurnal Kependudukan Indonesia, 2023)
The Covid-19 pandemic has caused a high number of layoffs in Indonesia. Laid-off workers have experienced decreasing financial capacity, so they need to be re-employed to meet their daily needs. Training is considered to be one solution to increase opportunities of re-employment as formal workers in the Covid-19 pandemic era, both Prakerja and Non-Prakerja trainings. This study aims to examine the effect of training on re-employment opportunities as formal workers for those who have been laid off due to the Covid-19 pandemic. This study employs binomial and multinomial regression models to analyse data from Sakernas August 2020 and 2021. The results show that only Non Prakerja training has increased the re-employment opportunities as formal workers. Meanwhile, Prakerja training has no significant impact on the re-employment in formal labour market, but only influenced re-employment opportunities as informal workers. The findings of this study suggest that trainings, particularly Non Prakerja, can be considered a solution to increase one’s opportunity for re-employment in formal sector. Meanwhile, Prakerja training plays an important role in accelerating workers’ skills improvement. In order to improve workers’ competency, they are expected to participate in various trainings, both by government and private sectors.